TINJAUAN ATAS KINERJA KEUANGAN MENGGUNAKAN RASIO KEUANGAN PADA PT UNILEVER INDONESIA TBK (PERIODE 2018-2022) - Halawa, Anugerah; Komarudin, Mochamad Fahru (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
The objective of this study is to assess the financial health of PT Unilever Indonesia Tbk during the 2018-2022 period by applying liquidity, solvency, and profitability ratio analyses. Employing a qualitative descriptive design, data were gathered through the documentation of annual financial statements sourced from the Indonesia Stock Exchange. The findings indicate that the company’s liquidity capacity remains sub-optimal as it falls below industry benchmarks. Furthermore, the reliance on external funding (debt) is significant, while profitability remains at a positive level despite the economic shocks caused by the Covid-19 pandemic. The primary recommendation of this research is the need for optimizing current assets and restructuring debt to ensure long-term stability.